Dissolution improvement of solid self-emulsifying drug delivery systems of fenofi brate using an inorganic high surface adsorption material - Shazly Gamal; Mohsin Kazi (Acta Pharmaceutica)
Solidification of lipid formulations using adsorbents is a recent technique attracting great interest due to its favourable properties including flexibility in dose division, reduction of intra-subject and inter-subject variability, improvement in efficacy/safety profile and enhancement of physical/ chemical stability. The current study aims to convert liquid self-emulsifying/nanoemulsifying drug delivery systems (SEDDS/SNEDDS) into solid SEDDS/SNEDDS and to assess how adsorption of the drug onto an inorganic high surface area material, NeusilinR grade US2 (NUS2), affects its in vitro dissolution performance. Lipid formulation classification systems (LFCS) Type III formulations were designed for the model anti-cholesterol drug fenofibrate. NUS2 was used to solidify the SEDDS/SNEDDS. Particle size and SEM analyses of solid SEDDS/SNEDDS powder were carried out to investigate the adsorption efficiency. In vitro dissolution studies were conducted to compare the developed formulations with the marketed product. The results of characterization studies showed that the use of 50 % (m/m) adsorbent resulted in superior flowability and kept the drug stable is amorphous state. Dissolution studies allow the conclusion that the formulation containing a surfactant of higher water solubility (particularly, Type IIIB SNEDDS) has comparably faster and higher release profiles than Type IIIA (SEDDS) and marketed product